New indicators of global integration using input-output analysis - Dongseok Kim (KDI Journal of Economic Policy, 2024)
The import content of export (ICE) has served as an indicator of global integration for several decades. It is defined as the share of imported products embodied in exports and can be interpreted as the relative degree of the utilization of global production network (GPN) over the domestic supply chain (DSC) in terms of "value-added." This paper proposes two new indicators of global integration. They are defined as the ratios of imports (foreign products) to gross output (domestic products) generated by exports and can be interpreted as the relative degrees of the utilization of GPN over DSC in terms of "production." Both indicators are easy to compute and can be compared between years, between countries, between industries, and between groups of industries. The paper applies the new indicators to the recent edition of the OECD's Input-Output Database. Finally, the paper shows that the recent slowdown in international trade is mostly due to the decrease in the international trade of intermediate goods, with significant implications regarding the future of global integration.
Keywords: F15; F14; D57; 330; New Indicators of Global Integration; Import Content of Export; Input-Output Analysis; OECD's Input-Output Database (OECD IO-DB)